112 A Propensity Matched Study of Return to Work Outcomes after Percutaneous Coronary Intervention and Coronary Artery Bypass Graft Surgery. (6th June 2015) - Maznyczka, Annette; Howard, James; Banning, Amerjeet; Gershlick, Anthony
Abstract : Background: Coronary heart disease can cause premature disability, and hence socioeconomic problems. A better understanding of return to work (RTW) after percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG), may help inform patients once other factors have been taken into account and both procedures deemed equally efficacious. Whilst some beliefs may be intuitive previous observational studies of RTW did not use propensity matching to minimise selection bias and strengthen causal inferences. This study aimed to consider: (i) RTW, (ii) employment status > 12 months post procedure and (iii) time taken to RTW, in patients treated with PCI or CABG. Methods: RTW questionnaires were sent to 169 CABG and 689 PCI patients, from a total 2323 patients, who had CABG or PCI at University Hospitals of Leicester from May 2012 to May 2013. 1465 patients were excluded, due to age >65, death, concomitant valve surgery, unsuccessful PCI, or non-UK or prison address. Responses from patients employed pre-procedure were analysed using multivariate logistic regression. Propensity score matching was also used to compare CABG and PCI, in a cohort balanced with regard to procedural urgency, cardiac rehabilitation, sex, age, ethnicity, living alone, ejection fraction, and pre-procedural job characteristics. Statistics were performed using R version 3.1.2. Results: The response rate was 38% (323 patients (88 CABG and 235 PCI patients)). Table 1 shows characteristics of respondents who were employed pre-procedure. Early retirement was the most frequent reason for unemployment post procedure (Figure 1 ). 241 respondents (75%) were employed pre-procedure. Of these 51 (77%) CABG and 162 (93%) PCI patients returned to work (p = 0.002). At >12 months 41 (62%) CABG and 147 (84%) PCI patients were still employed (p = 0.0001). However, after using propensity scores to select a balanced cohort of 32 pairs, there was no significant difference between PCI and CABG patients in RTW (p = 1.000), nor long term employment, i.e. >12 months (p = 0.756). The factors that were significantly associated with RTW after multivariate analysis (MVA) were younger age, not having diabetes mellitus (DM), good ejection fraction and not being self-employed. After MVA younger age and not having DM remained significantly associated with long term employment. The median time taken to RTW was 6 weeks after PCI and 13 weeks after CABG (p = 0.001). This effect remained significant on MVA (P = 0.001) and after propensity analysis (p = 0.001). Conclusion: This is the first propensity matched study comparing RTW after PCI or CABG procedures. The results suggest that younger age, not having DM, good ejection fraction and not being self-employed are the strongest predictors of RTW. PCI when compared to CABG predicts earlier RTW, but appears to have no impact on RTW rates, in this subset of patients, although factor selection for the propensity analysis may mask differences.